2012
DOI: 10.1128/mbio.00218-12
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Fusion Protein-Induced Toll-Like Receptor 4 (TLR4) Signaling Is Inhibited by the TLR4 Antagonists Rhodobacter sphaeroides Lipopolysaccharide and Eritoran (E5564) and Requires Direct Interaction with MD-2

Abstract: Respiratory syncytial virus (RSV) is a leading cause of infant mortality worldwide. Toll-like receptor 4 (TLR4), a signaling receptor for structurally diverse microbe-associated molecular patterns, is activated by the RSV fusion (F) protein and by bacterial lipopolysaccharide (LPS) in a CD14-dependent manner. TLR4 signaling by LPS also requires the presence of an additional protein, MD-2. Thus, it is possible that F protein-mediated TLR4 activation relies on MD-2 as well, although this hypothesis has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 55 publications
3
102
0
Order By: Relevance
“…Other studies in human colorectal and esophageal cancer cell lines have indicated that eritoran blocks LPS-induced TLR4 signaling for b1 integrin-and selectin-dependent cell adhesion and that it inhibits their migratory capability (54,55). Furthermore, eritoran has previously been shown to inhibit monocytic inflammatory responses in endotoxemic rats and virus-infected mice (22,29,30). The possibility that the inhibitory effect of eritoran on inflammatory cytokine production may help suppress tumor malignancy cannot be ruled out.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies in human colorectal and esophageal cancer cell lines have indicated that eritoran blocks LPS-induced TLR4 signaling for b1 integrin-and selectin-dependent cell adhesion and that it inhibits their migratory capability (54,55). Furthermore, eritoran has previously been shown to inhibit monocytic inflammatory responses in endotoxemic rats and virus-infected mice (22,29,30). The possibility that the inhibitory effect of eritoran on inflammatory cytokine production may help suppress tumor malignancy cannot be ruled out.…”
Section: Discussionmentioning
confidence: 98%
“…However, eritoran (with only 4 acyl chains) does not induce TLR4/MD2 complex dimerization or cytoplasmic signaling (27). Animal studies using eritoran have demonstrated an inhibition of proinflammatory TLR4 signaling, improvement of intestinal microcirculation, and higher survival rates in endotoxemic rodents (22,28) and in influenza-and syncytial virusinfected mice (29,30). However, whether eritoran binds to CD14 and triggers CD14-mediated apoptosis in colon cancer cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 forms a complex with MD-2 for efficient binding on the cell surface (43) and with CD14 for the internalization of TLR4 (35). MD-2 acts as a coreceptor for recognition of both exogenous ligands (43,44) and endogenous ligands (45,46). In addition, TLR4 can bind bacterial and viral PAMPs and, under inflammatory conditions, also endogenous damage-associated molecular pattern molecules (9).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4's role in recognition of needle proteins was less expected than that of the more promiscuous TLR2. However, there are several documented cases of TLR4 interaction with pathogen-associated substrates other than LPS, including respiratory syncytial virus (RSV) fusion protein (30), chlamydial Hsp60 (31), pneumolysin (32), Francisella tularensis DnaK (33), Ebola virus glycoprotein (34), and cell wall components from Pseudallescheria boydii (35). The interaction of these PAMPs and TLR4 are well known, and future research will hopefully elucidate how needle proteins interact with TLR4, including whether MD-2 or CD-14 is required for this interaction.…”
Section: Tlr2-expressing Hek-blue Cells Respond To Needle Proteinsmentioning
confidence: 99%